2015
DOI: 10.4238/2015.november.13.2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between interleukin-6 expression in articular cartilage bone and osteoarthritis

Abstract: ABSTRACT. This study aimed to investigate the expressional profile of interleukin-6 (IL-6) in articular cartilage bone of osteoarthritis (OA) patients and its correlation with OA. A total of 30 articular cartilage bone samples from knee OA patients, which were collected by knee arthroscopy or articular surgery, comprised the study group, and 30 samples of normal articular cartilage tissue comprised the control group. Both mRNA (messenger ribonucleic acid) and protein levels of IL-6 and matrix metalloproteinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Cartilage degeneration is usually mediated by the action of the enzymes, MMPs and ADAMTSs, which degrade collagen and aggrecan of the cartilage extracellular matrix (Murphy and Lee, 2005). Studies have shown that human OA cartilage exhibits enhanced production of MMP1, 2, 3, 8, 9, 13, TNF-α, IL-1β, IL-6, and ADAMTS-4, 5 (Tetlow et al, 2001;Malfait et al, 2002;Qu et al, 2015). In the in vitro OA model reported here, we observed similar changes, thus validating the physiological relevance of the human cell-based OC chip OA model.…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage degeneration is usually mediated by the action of the enzymes, MMPs and ADAMTSs, which degrade collagen and aggrecan of the cartilage extracellular matrix (Murphy and Lee, 2005). Studies have shown that human OA cartilage exhibits enhanced production of MMP1, 2, 3, 8, 9, 13, TNF-α, IL-1β, IL-6, and ADAMTS-4, 5 (Tetlow et al, 2001;Malfait et al, 2002;Qu et al, 2015). In the in vitro OA model reported here, we observed similar changes, thus validating the physiological relevance of the human cell-based OC chip OA model.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of a variety of inflammatory factors plays an important role in formation and development of osteoarthritis [21]. Among these inflammatory factors, IL-1, IL-6 and TNF-α are critical [22][23][24][25]. These cytokines disrupt articular cartilage by promoting the synthesis and release of matrix metalloproteinases, degrading cartilage matrix, inducing chondrocyte apoptosis and reducing extracellular matrix synthesis [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Forty eight healthy New Zealand rabbits (body weight 2.5~3.5 kg, male (24) and female (24)) were provided by the Shanghai Songjiang District Songlian experimental animal company, license number: SCXK (Shanghai) 2012-0011. Fujian University of Traditional Chinese Medicine Experimental Animal Center provided clean medical laboratory animal environmental facilities; license number SCXK (Min) 2012-0001.…”
Section: Animalsmentioning
confidence: 99%
“…Genetic studies have indicated that the susceptibility to RA has a genetic component (Choi et al, 2006). The genes coding for several cytokines are believed to be associated with autoimmune disease (Seldin et al, 1999;Qu et al, 2015), while other such genes may not be correlated with it (Zhu et al, 2013;Ye et al, 2015). Our previous studies have led to the discovery of several single nucleotide polymorphisms (SNPs) in genes coding for various cytokines, including interleukin-10 (IL-10), , that are correlated with RA (Ge et al, 2015;Shen et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%